Efeito neuroprotetor do antagonismo do receptor P2X7 no Parkinsonismo experimental induzido por 6-OHDA - Carmo, Marta Regina Santos do (2015)
Parkinson’s disease (PD) is characterized by a progressive degeneration of dopaminergic neurons in the substantia nigra (SN) and a concomitant decrease of dopamine (DA) in the striatum, which can be modeled by 6-OHDA administration. Since ATP released from damaged cells can exert noxious effects on neurons, acting through its P2X7 receptors (P2X7R), the aim of the present study was to investigate the effects of a P2X7R antagonist, Brilliant Blue G (BBG) on 6-OHDA-induced neurotoxicity. Male Wistar rats received stereotaxic injections of 6-OHDA (18 µg/3µl) into the right striatum and were treated with BBG (45 mg/kg, i.p. 48/48 h) for two weeks. In an additional experiment, animals were treated with the selective antagonist A-438079 (10 µM i.c.v.) for two weeks. BBG decreased the number of contralateral rotations in the apomorphine test, an effect mimicked by the selective P2X7R antagonist A438079. BBG has also improved the animals’ performance in the passive avoidance test (short-term memory) and in the cued version of the Morris Water maze. The antagonism of P2X7R by BBG has also prevented the reduction of dopamine content in the striatum and SN as well as the loss of dopaminergic neurons, and microgliosis and astrogliosis in the striatum. BBG treatment also decreased the IL-1β levels in striatum, despite the observed effect not being statistically significant. To grasp the mechanism of action of BBG, we used in vitro models exploring synaptotoxicity (striatal synaptosomes) and neurotoxicity (dopamine-differentiated SH-SY5Y cells). Besides showing that P2X7R are present in striatal dopaminergic terminals, we observed that BBG 100 nM prevented the 6-OHDA-induced synaptosomal dysfunction. Furthermore, we have shown the presence of P2X7 receptors in SH-SY5Y cells, their co-localization with tyrosine hydroxilase, and that BBG attenuates the cell damage, evaluated through lactate dehydrogenase release. The present results suggests that P2X7R contribute to PD pathogenesis through a triple impact on synaptotoxicity, gliosis and neurotoxicity, highlighting the therapeutic potential of P2X7R antagonists in the disease.